2023
DOI: 10.1002/ecs2.4736
|View full text |Cite
|
Sign up to set email alerts
|

Impact of typical land use type on the stability and content of carbon and nitrogen of soil aggregates in western Hubei

Ting Luo,
Lu Xia,
Dong Xia
et al.

Abstract: In order to investigate the characteristics of soil structural stability and the factors influencing it under typical land use types in the karst region of western Hubei, soil samples were collected from five land use types (natural mixed forest [NF], cypress forest [CF], stone dike terrace [ST], stone dike forest [SF], and abandoned land [AL]) in Xialaoxi to analyze the particle size distribution of aggregates, structural stability, and the distribution characteristics of carbon, nitrogen, and extracellular e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Zhu et al (2017) note that the greatest differences between soils of different types of land use were found in the content of aggregates of fractions 2-5, 1-2, 0.25 mm. This indicates a greater indicator value of aggregates of fractions < 2 mm compared to aggregates of fractions >2 mm (Luo et al, 2023). The existence of close direct relationships between the sand content and the content of water-stable aggregates of the 3-5 mm (r = 0.74-0.96) and 2-3 mm (r = 0.70-0.93) fractions has been established.…”
Section: Discussionmentioning
confidence: 67%
“…Zhu et al (2017) note that the greatest differences between soils of different types of land use were found in the content of aggregates of fractions 2-5, 1-2, 0.25 mm. This indicates a greater indicator value of aggregates of fractions < 2 mm compared to aggregates of fractions >2 mm (Luo et al, 2023). The existence of close direct relationships between the sand content and the content of water-stable aggregates of the 3-5 mm (r = 0.74-0.96) and 2-3 mm (r = 0.70-0.93) fractions has been established.…”
Section: Discussionmentioning
confidence: 67%
“…Yang et al (2024) note an increase in the content of aggregates of the > 2 mm fraction during the restoration of forest vegetation, especially in the 0-40 cm layer. Luo et al (2023) found an increased content of aggregates of the > 2 mm fraction in forest soils. Thus, the content of aggregates of the fraction > 2 mm can be used as an indicator of the influence of forest vegetation on the aggregate composition of chernozems.…”
Section: Discussionmentioning
confidence: 86%